Compact and highly active next-generation libraries for CRISPR-mediated gene repression and activation - Horlbeck, Max A; Gilbert, Luke A; Villalta, Jacqueline E; Adamson, Britt; Pak, Ryan A; Chen, Yuwen; Fields, Alexander P; Park, Chong Yon; Corn, Jacob E; Kampmann, Martin; Weissman, Jonathan S (eLife, 2016)
We recently found that nucleosomes directly block access of CRISPR/Cas9 to DNA (Horlbeck et al., 2016 ). Here, we build on this observation with a comprehensive algorithm that incorporates chromatin, position, and sequence features to accurately predict highly effective single guide RNAs (sgRNAs) for targeting nuclease-dead Cas9-mediated transcriptional repression (CRISPRi) and activation (CRISPRa). We use this algorithm to design next-generation genome-scale CRISPRi and CRISPRa libraries targeting human and mouse genomes. A CRISPRi screen for essential genes in K562 cells demonstrates that the large majority of sgRNAs are highly active. We also find CRISPRi does not exhibit any detectable non-specific toxicity recently observed with CRISPR nuclease approaches. Precision-recall analysis shows that we detect over 90% of essential genes with minimal false positives using a compact 5 sgRNA/gene library. Our results establish CRISPRi and CRISPRa as premier tools for loss- or gain-of-function studies and provide a general strategy for identifying Cas9 target sites.